The Campus Canopy, 1938-12-02 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1938)
The Campus Canopy, December 2, 1938. Vol. 7, No. 10. -- Examination Schedule Is Posted By Durrenburger -- Freshmen Elect Graham And Culpepper -- Hanging Of The Green Will Take Place Sunday -- Kraft Will Present Last Recital Sunday -- Sports Council Schedules Dates For Tournaments -- Eight Students Receive Mention -- IRC Will Feature Magazine Articles At Monday Forum -- Rev. Thompson Speaks At Chapel On Right & Wrong -- Durrenburger Named President -- Seven Receive Alpha Delta Bids -- Wilson Heads Math Club Meeting -- Thanks For The Memories
Georgia State Womans College Student Newspaper
Digitized from original print, Valdosta State University Archives and Special Collections, November 29, 2016.
Keywords: Valdosta State University -- Periodicals